Cover Image, Volume 53, Issue 2. (27th February 2020) - Xu, Hongyuan; Zhou, Siru; Qu, Ranyi; Yang, Yiling; Gong, Xinyi; Hong, Yueyang; Jin, Anting; Huang, Xiangru; Dai, Qinggang; Jiang, Lingyong
Abstract : The cover image is based on the Original Article Icariin prevents oestrogen deficiency–induced alveolar bone loss through promoting osteogenesis via STAT3 by Hongyuan Xu et al., https://doi.org/10.1111/cpr.12743 .